Determinants of home delivery among reproductive age women in Bore District, East Guji Zone, Ethiopia: a case–control study - Teressa, Beka; Legesse, Elsabeth; Nigussie, Tadesse; Deriba, Berhanu Senbeta; Guye, Ararso Hordofa; Girma, Derara; Dejene, Hiwot; Adugna, Leta; Birhanu, Belete; Eshetu, Hana; Tadele, Amanu’el; Mideksa, Gachena (Frontiers in Global Women's Health, 2024)
Introduction: Home delivery is a type of childbirth at one's residence rather than a health facility, and this is a major reason for maternal mortality caused by obstetric complications such as sepsis, hypertensive disorders, and hemorrhage., sMaternal and child mortality is still high in developing countries, despite the efforts made to reduce the same. This is mainly due to poor utilization of institution-based health care services. Moreover, limited studies addressed the determinants of home delivery in Ethiopia, including the study area. The study aimed at identifying determinants of home delivery in Bore district, East Guji Zone, Southern Ethiopia,Methods: A community-based unmatched case-control study was conducted from May 18 to July 5, 2022 among 498 women (249 cases and 249 controls)who gave birth in Bore district.Cases were women who gave birth at homewhile controls were those women who gave their last birth at health institutions. Multistage sampling technique was employed in selecting study participants. Data were collected using Kobo Toolbox digital software and exported to SPSS version 26.0 for analysis. Multivariable logistic regression analysis was done to declare the statistical significance of the association of the the independent variables and home delivery.Results: A total of 496 respondents were included in the study with a mean age of 32.5 (SD = ±5.5) for cases and 33.7 (SD= ±5.2) for controls. Of the assessed determinants of home delivery; not attending ANC visit (AOR= 5.6, 95% CI: 2.0-15.16), not attending pregnant mother's conference (AOR=3.2, 95% CI: 1.65-8.32), not received health education on pregnancy-related complications (AOR:=2.2, 95% CI: 1.1-4.3), inadequate knowledge about pregnancy-related danger signs (AOR= 6.0, CI: 3.0-11.9), inadequate knowledge about pregnancy-related complications (AOR=3.0, CI: 1.55-6.13), and unfavorable attitude (AOR=6.9, 95% CI: 2.16-22.6) were identified as determinants of home delivery.In this study, not attending ANC visits, missing pregnant mother's conference, not receiving health education on pregnancy-related complications, inadequate knowledge about pregnancy-related danger signs, inadequate knowledge about pregnancy-related complications, and unfavorable attitudes were identified as determinants of home delivery.